The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000027426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial peptide LL-37 for treatment of Staphylococcus aureus biofilm on titanium plate

Abstract: The antimicrobial peptide LL-37 belongs to the cathelicidin family and is one of the few human bactericidal peptides with potent antistaphylococcal activity. Staphylococcus aureus is one of the main infection bacteria in orthopedic implant therapy. Biofilm formation after bacterial infection brings more and more severe test for clinical antiinfection treatment.However, there are few studies on LL-37 in S. aureus infection of prosthesis. In this work, addition to research the antibacterial activity and the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Thus, an antimicrobial effect of the herein described peptides would be highly beneficial for a future treatment of these critical pathogens. As controls, we included not only MGD2 but also LL37, which was very recently investigated concerning its potency to prevent S. aureus biofilm formation on titanium alloy surfaces 24 . After incubating the peptides for 2 h with the respective strains, a colony formation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an antimicrobial effect of the herein described peptides would be highly beneficial for a future treatment of these critical pathogens. As controls, we included not only MGD2 but also LL37, which was very recently investigated concerning its potency to prevent S. aureus biofilm formation on titanium alloy surfaces 24 . After incubating the peptides for 2 h with the respective strains, a colony formation assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…As controls, we included not only MGD2 but also LL37, which was very recently investigated concerning its potency to prevent S. aureus biofilm formation on titanium alloy surfaces. 24 After incubating the peptides for 2 h with the respective strains, a colony formation assay was performed. For all tested peptides, a steady decrease in bacterial viability of S. aureus was observed (Figure 2).…”
Section: Namementioning
confidence: 99%
“…The human cathelicidin LL-37 was one of the popular AMPs to be studied during the review period, with LL-37 being one of the few human bactericidal peptides with potent anti-staphylococcal activity (one of the main bacteria associated with orthopeadic implant infections). Using in vitro studies and static biofilm models, Wei et al showed that LL-37 had significant anti-staphylococcal effects and a 'destructive effect' on S. aureus biofilm formed on a titanium alloy surface (as a proxy for a prosthesis) [99]. Wuersching et al examined the effects of LL-37 and human lactoferricin AMPs on anaerobic biofilms associated with oral diseases [100].…”
Section: Amp Type 251 Single Amp Typementioning
confidence: 99%
“…The best-studied NAMP produced in the human body is cathelicidin LL-37, termed host defence enzymes, which possesses antimicrobial and antibiofilm activities against a broad spectrum of MDR strains [ 171 , 217 ]. A large number of studies regarding antimicrobial/antibiofilm properties of the LL-37 are focused on strains in which antibiotic resistance is a serious problem, including P. aeruginosa [ 218 ], S. aureus [ 219 ], S. epidermidis [ 220 ], Streptococcus pneumoniae [ 221 ], Streptococcus pyogenes [ 222 ], Acinetobacter baumannii [ 223 ], E. coli [ 224 ], K. pneumonia [ 225 ], Helicobacter pylori [ 226 ], and Aggregatibacter actinomycetemcomitans [ 227 ]. In P. aeruginosa PAO1 grown under biofilm conditions in a flow cell, global gene expression analysis revealed that 4-day exposure to LL-37 (4 µg/mL) led to the downregulation of 475 genes, including QS-controlled genes such as lasl and rhlR [ 228 ].…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%